Hubungan Antara Karateristik Pekerjaan Dengan Motivasi Kerja Karyawan PT. Pionirbeton Plant Cimareme Bandung - Dewi Puspasari; Evi Sri Nurhastuti; Pradiptya Septyanti Putri (LPPM UNIBI, 2021)
Which factors are low work ability, misguided work. Whether or not there is, the large or small existence between the numbers is very up to the perception of the perception of employees. This research aims to know about the tightness of the relationship between the work and farming staff of employees of PT Perintisbeton Indutri Plant Cimareme Bandung. The hypothesis behind this study is again the negative perception of employees about the function of their work, the lower the average work. The first variable in this study is work and work is also how it works. The measuring instrument that since for the characteristics of the work using JCS (Scale of Work Characteristics) was first born by Hackman and Oldham (1980) and then some were exiled by Maymanah, et al., (2018) as many as 12 items. And for variable mingling work, the instrument by which the construction of the measuring instrument is located kinlaw theory (1981), which the researchers did on its fumes, this scale contains 26 items. This research is a life research initiative. Life that is carried out in this research is the employees of PT Perintisbeton Indutri Plant Cimareme Bandungumber of 60 people. For those who know the relationship between variables jakarta using